MTUN Advanced TVET and Ministry of Higher Education delegation strengthen ties and explore WBL with HSKL - Nur Ezzati, Mohd Nasir (UMPSA, 2024)
KAISERSLAUTERN, GERMANY, 22 May 2024 - The Malaysia Technical University Network (MTUN) Advanced TVET delegation, together with the Ministry of Higher Education, led by the Minister of Higher Education, Dato' Seri Diraja Dr. Zambry Abd Kadir, undertook a strategic visit to the University of Applied Sciences Kaiserslautern (HSKL), Germany.